Integrative analysis of genomic and transcriptomic characteristics associated with progression of aggressive thyroid cancer - Seong-Keun Yoo (Nature Portfolio, 2019)
Anaplastic thyroid cancer (ATC) and advanced differentiated thyroid cancers (DTCs) come with a dismal prognosis. Here, Yoo and colleagues reveal the genomic and transcriptomic landscape of ATC and DTC, highlighting potential therapeutic vulnerabilities.